THE EFFECT OF USING PHYSICS LEARNING VIDEO INTEGRATED ELECTRONIC LKS ON STUDY PROGRAM IN CLASS XI FLUID MATERIAL - Afra Asysyaa Fitri; Desnita Desnita (Universitas Negeri Padang, 2023)
This study aims to see the effect of using integrated electronic video worksheets on physics learning on KPS in class XI fluid materials at SMAN 1 Pulau Punjung. The subjects of this study were all learners of class XI MIPA at SMAN 1 Pulau Punjung. The sample was taken out using a purposive cluster sampling technique, selecting class XI MIPA 1 as the experimental class and XI MIPA 2 as the control class. The study instrument was a written test including 30. The data research technique used in the hypothesis test is the t-test. The results showed that the average science process skills of students in the experimental class were taller than those in the control class. The results of assumption testing using the t-test, received ???? count of 4.393 and ???????????????????????? with a significance level of 0.05 with a table value of 1.668. So, it can be deduced that there is an influence of the use of video-integrated electronic worksheets on science process skills in fluid material for class XI SMAN 1 Pulau Punjung.